OFET Preparation by Lithography and Thin Film Depositions Process - Sujarwata Sujarwata; Fianti Fianti; Langlang Handayani; Aji Purwinarko; Susilo Susilo (Universitas Ahmad Dahlan, 2018)
The length of the channel OFET based thin film is determined during preparation takes place using the technique of lithography and mask during the metal deposition process. The lithography technique is the basic process steps in the manufacture of semiconductor devices. Lithography is the process of moving geometric shapes mask pattern to a thin film of material that is sensitive to light. The pattern of geometric shapes on a mask has specifications, as follows: long-distance source and drain channels varied, i.e. 100 μm, the width of the source and drain are made permanent. Bottom contact OFET structure has been created using a combination of lithography and thin film deposition processes.